Unlawful for a Jew? Acts 10:28 and the Lukan View of Jewish-Gentile Relations - Schaser, Nicholas J. (Biblical theology bulletin, 2018)
Most scholars read Peter's claim that it is unlawful for Jews to associate with Gentiles (Acts 10:28a) as an accurate statement on Jewish-Gentile relations according to Luke. However, Luke problematizes this view by showing Peter to be unaware of Jewish-Gentile interactions that preceded him, both in Israel's Scriptures and Luke-Acts. Rather than reflecting the exclusionary state of pre-Christian Judaism, Acts 10:28a constitutes a fallacy that Luke invalidates via intertextual references to ethnic inclusivity throughout biblical history. Peter's misunderstanding provides Luke with the theological rationale for Paul to take the missionary mantle from Peter as the apostle to the Gentiles.